2016
DOI: 10.2147/copd.s110746
|View full text |Cite
|
Sign up to set email alerts
|

Invasive coronary angiography in patients with acute exacerbated COPD and elevated plasma troponin

Abstract: BackgroundIn acute exacerbation of COPD, increased plasma levels of cardiac troponin are frequent and associated with increased mortality. Thus, we aimed at prospectively determining the diagnostic value of coronary angiography in patients with exacerbated COPD and concomitantly elevated cardiac troponin.Patients and methodsA total of 88 patients (mean age 72.9±9.2 years, 56.8% male) hospitalized for acute exacerbation of COPD with elevated plasma troponin were included. All patients underwent coronary angiogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 27 publications
2
15
0
2
Order By: Relevance
“…45,46 In a cohort study performed in patients with severe exacerbations of COPD and elevated levels of troponins at admission, coronary angiography performed 72 hours after hospitalization showed significant coronary stenosis (>50%) in major coronary arteries in 67% of patients, of which 39% required percutaneous coronary intervention. 47…”
Section: Serum Biomarkersmentioning
confidence: 99%
“…45,46 In a cohort study performed in patients with severe exacerbations of COPD and elevated levels of troponins at admission, coronary angiography performed 72 hours after hospitalization showed significant coronary stenosis (>50%) in major coronary arteries in 67% of patients, of which 39% required percutaneous coronary intervention. 47…”
Section: Serum Biomarkersmentioning
confidence: 99%
“… 14 , 30 Moreover, patients admitted for COPD exacerbation were found to have a high troponin level in the absence of acute coronary symptoms and a subsequent coronary angiography showed significant coronary stenosis. 31 A recent extended follow-up study on patients with CAD showed persistent increase of cardiovascular mortality in patients with coexisting COPD. 32 Additionally, when treating patients who are diagnosed with both COPD and CAD, the long-term use of beta-2 agonists is considered a safe practice, 33 and the use of cardio-selective beta-blockers in CAD may even lower the mortality of patients with COPD.…”
Section: Discussionmentioning
confidence: 99%
“…Also, cardiovascular disease is a frequent comorbidity and a significant cause of morbidity and mortality in COPD patients ( 40 - 44 ). In patients with AECOPD and an elevated troponin I level, coronary angiography confirmed ischemic heart disease in 67%, and 38.6% required a coronary revascularization ( 42 ). In our patients, additional diagnostic evaluation (echocardiography, coronary angiography, and CT pulmonary angiography) was performed to exclude acute coronary incident or pulmonary embolism.…”
Section: Discussionmentioning
confidence: 99%